“Let’s try this again”: Exploring the Potential of Virtual Reality in Providing Effective Practice Cycles - Hernández González, Teresa; Arora, Remi; Luna Barahona, Marco; Bakarally, Shehrazade (Apprendre et enseigner aujourd’hui)

(untitled) (Conseil pédagogique interdisciplinaire du Québec, 2024)
The demanding initiation into the teaching profession contributes significantly to attrition rates among teachers. Virtual reality (VR), a tool proven to be effective in other professions, offers a controlled and safe environment for developing teaching expertise, potentially mitigating attrition. The Teaching English as a Second Language (TESL) program and the Lab for Innovation in Teaching and Learning (LITL) at Concordia University have created a proof-of-concept Minimal Viable Product (MVP) VR tool for teacher education, piloting it with student teachers from diverse programs and partner universities. The MVP immerses participants in a post-observation meeting scenario that is typically loaded with interpersonal and emotional challenges. Initial testing indicated VR's potential to evoke the emotional and cognitive engagement necessary for effective deliberate practice cycles. We present our journey so far and highlight the design dilemmas and challenges. The overarching goal of our project is to foster innovation in teacher education while establishing a network of professionals motivated to reduce attrition rates by facilitating teacher training and better equipping student teachers for their initiation in the profession.